2022
DOI: 10.3389/fnhum.2022.782579
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Abnormalities on Proton MR Spectroscopy and Imaging in Patients With Gluten Ataxia: A Pilot Study

Abstract: Gluten ataxia is a rare immune-mediated neurological disorder caused by the ingestion of gluten. The diagnosis is not straightforward as antibodies are present in only up to 38% of patients, but often at lower titers. The symptoms of ataxia may be mild at the onset but lead to permanent damage if remain untreated. It is characterized by damage to the cerebellum however, the pathophysiology of the disease is not clearly understood. The present study investigated the neurochemical profile of vermis and right cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In the study of Rawat et al on GA, there were lower N-acetyl aspartate (tNAA: N-acetylaspartate + N-acetylaspartate glutamate) and choline (tCho: glycerylphosphorylcholine + phophocholine) amounts in the vermis and right cerebellum [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Rawat et al on GA, there were lower N-acetyl aspartate (tNAA: N-acetylaspartate + N-acetylaspartate glutamate) and choline (tCho: glycerylphosphorylcholine + phophocholine) amounts in the vermis and right cerebellum [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…SCAs primarily affect the cerebellum and spinal cord but may also cause degeneration in other parts of the central nervous system [ 7 ]. Gluten ataxia (GA), a rare immune-mediated cerebellar ataxia (IMCA), is a neurological presentation of gluten sensitivity enteropathy and can be demonstrated (although non-specifically) through the concentration of antigliadin antibodies in the blood serum [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ataxia's early signs may be subtle, but worsen if left untreated. In a study by Rawat et al (2022), patients with gluten ataxia were analyzed for structural alterations in different parts of the brain as well as their neurochemical profile in the vermis and right cerebellum. Patients with gluten ataxia had smaller lobes (X) of the cerebellum and thalamus, as well as larger lateral ventricles, compared to healthy controls.…”
Section: Neurological Manifestations Of CDmentioning
confidence: 99%
“…Patients with gluten ataxia had smaller lobes (X) of the cerebellum and thalamus, as well as larger lateral ventricles, compared to healthy controls. Neuronal degeneration was likely present in patients with gluten ataxia, as evidenced by decreased neuronal metabolites and anatomical alterations in the brain [24].…”
Section: Neurological Manifestations Of CDmentioning
confidence: 99%
“…On the other hand, anti-TG6 antibodies were presented in 32% of patients with negative tests for other serological markers of GRD, which makes diagnosis a challenge. Because of this great variation in the prevalence of serological evidence or even its absence, the evaluation of the presence of cerebellar atrophy, usually present in up 60% of GA patients, has been more frequently performed for GA diagnosis through magnetic resonance imaging (MRI) and spectroscopy (MRS) (Hadjivassiliou et al, 2015), that was the focus of the study carried out by Rawat et al (2022) (Rawat et al, 2022). This eligible study showed cerebellar atrophy in all GA patients (aged from 40-60 years) with no neurological/psychiatric diseases and no medical or family history of ataxia and with weak serological evidence for GRD (66.6% positive IgA anti-AGA and 16.6% positive anti-TG6 and anti-tTG2).…”
Section: Characteristics Of Publication Outputsmentioning
confidence: 99%